DORMANCY BREAKING OF OIL PALM SEED TENERA VARIETY BY SOAKING FOR A CERTAIN LENGTH OF TIME IN THE SULFURIC ACID SOLUTION - SUENA, WAYAN (Agrotrop : Journal on Agriculture Science; Vol 1 No 2 (2011))
The experiment aimed to know the effect of length of soaked time in sulfuric acid (H2SO4) solution to the dormancy breaking upon the oil palm seeds. The experiment show that soaking seeds for 12 and 10 minutes in the acid solution resulted dormancy breaking were reached after 61.3 days, while soaking seed for 2 minutes in the same solution breaking of dormancy was reached after 73.5 days. By soaked oil palm seeds in sulfuric acid solution gave highest germination percentage (80%), peak value of germination was 0.77%/day, by an average of 0.73%/day. So that, by soaked oil palm seed in sulfuric acid solution for 12 minutes was able to increase vigor, viability, rate of germination and growth uniformity.
Keywords: dormancy, oil palm seed, soaked, sulfuric acid solution